fatore os seguintes polinomios
B ) 4xy+8xy+12x
C ) 3y²-6y elevado a 3+9y
D )2x elevado a 3-6y elevado a 3+9y
Soluções para a tarefa
Respondido por
3
B ) 4xy+8xy+12x = 4x(y +2y +3)
C ) 3y²-6y elevado a 3+9y
![(3y^2-6y)^3+9y=9 y (3 y^5-18 y^4+36 y^3-24 y^2+1)=\\
27 (y-2)^3 y^3+9 y (3y^2-6y)^3+9y=9 y (3 y^5-18 y^4+36 y^3-24 y^2+1)=\\
27 (y-2)^3 y^3+9 y](https://tex.z-dn.net/?f=%283y%5E2-6y%29%5E3%2B9y%3D9+y+%283+y%5E5-18+y%5E4%2B36+y%5E3-24+y%5E2%2B1%29%3D%5C%5C%0A27+%28y-2%29%5E3+y%5E3%2B9+y)
D )2x elevado a 3-6y elevado a 3+9y
![(2x)^3-6y^3+9y=2 x^3+y (9-6 y^2) (2x)^3-6y^3+9y=2 x^3+y (9-6 y^2)](https://tex.z-dn.net/?f=%282x%29%5E3-6y%5E3%2B9y%3D2+x%5E3%2By+%289-6+y%5E2%29)
C ) 3y²-6y elevado a 3+9y
D )2x elevado a 3-6y elevado a 3+9y
Respondido por
4
B ) 4xy+8xy+12x
4x(y + 2y + 12)
4x (3y+12)
C ) 3y²-6y elevado a 3+9y
3y² -6y³ +9y
3y(-2y²+y+3)
D )2x elevado a 3-6y elevado a 3+9y
2x³-6y³ + 9y
2x³ + 3y(-2y²+3)
4x(y + 2y + 12)
4x (3y+12)
C ) 3y²-6y elevado a 3+9y
3y² -6y³ +9y
3y(-2y²+y+3)
D )2x elevado a 3-6y elevado a 3+9y
2x³-6y³ + 9y
2x³ + 3y(-2y²+3)
Perguntas interessantes